THE ROLE OF AI IN MANAGING PROJECT RESOURCES IN PAKISTAN - Sain, Zohaib Hassan (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
This research examines the changing role of artificial intelligence (AI) in managing project resources, specifically in Pakistan. The objective is to determine the potential contributions of AI to PRM and its ability to aid managers in making well-informed choices. In recent times, Artificial Intelligence (AI) has emerged as a disruptive and influential factor in different technological domains, posing a challenge to existing conventions in multiple sectors. This study primarily investigates the unique circumstances of PRM (Public Relations Management) in Pakistan, where the possible ramifications of AI (artificial intelligence) still need to be comprehensively grasped. We use a quantitative study methodology to examine the difficulties encountered by project managers in the realm of resource management, as well as the potential benefits that artificial intelligence (AI) might provide in enhancing their decision-making procedures. The technique included distributing a survey to 220 persons, primarily skilled in project management, with a significant presence of younger age cohorts, highlighting the growing significance of AI adoption among the younger demographic. Many participants also have experience in project management or similarly connected areas. The results imply a connection between PRM and AI use, although it lacks statistical significance. This means a possible association that requires additional examination using a more extensive dataset. Future research on the influence of AI on PRM in Pakistan should use a larger and more comprehensive sample size. This study highlights AI's ever-changing and influential role in PRM (Public Relations Management). It emphasizes the need for ongoing investigation and adaptation to use its capabilities thoroughl